Job quality and digitalisation - Agnieszka Piasna (European Trade Union Institute (ETUI), 2024)
This working paper examines the impact on job quality of new digital technologies at work. It applies the multidimensional framework of the ETUI Job Quality Index to an analysis of the 27 EU Member States and data from the 2021 European Working Conditions Telephone Survey. The effects of digitalisation are conceptualised on the basis of two theoretical approaches: one considers the impact of computerised systems and algorithmic management on task allocation, working time and work intensity; the other looks at digitalisation at work in terms of job demands and resources. The analysis examines how the use of computerised systems at work and their influence on the content and organisation of work affect different dimensions of job quality and how this may differ across groups of workers.
Keywords: 330; Digitalisierung; Arbeitsbedingungen; Arbeitsgestaltung; Arbeitszeit; EU-Staaten